Fabricating CAD/CAM Implant-Retained Mandibular Bar Overdentures: A Clinical and Technical Overview - Chui Ling Goo; Keson Beng Choon Tan (Hindawi Limited, 2017)
This report describes the clinical and technical aspects in the oral rehabilitation of an edentulous patient with knife-edge ridge at the mandibular anterior edentulous region, using implant-retained overdentures. The application of computer-aided design and computer-aided manufacturing (CAD/CAM) in the fabrication of the overdenture framework simplifies the laboratory process of the implant prostheses. The Nobel Procera CAD/CAM System was utilised to produce a lightweight titanium overdenture bar with locator attachments. It is proposed that the digital workflow of CAD/CAM milled implant overdenture bar allows us to avoid numerous technical steps and possibility of casting errors involved in the conventional casting of such bars.